Monitoring Pathophysiology in the Injured Brain - Eric P. Thelin (Frontiers Research Topics, 2018)
Pathophysiological processes in brain-injured patients can be assessed with an array of methods, with a goal to identify potentially deleterious events, guide treatments and avoid further deterioration. This eBook provides an in-depth exploration into different aspects of neuro-critical care monitoring and how new tools and strategies may be utilized to improve patient outcomes.